Synthesis methods of 1,2,3-/1,2,4-triazoles: A review - Dai, Jinlian; Tian, Sen; Yang, Xueqing; Liu, Zongliang (Frontiers in Chemistry, 2022)
Triazole including three nitrogen atoms and two carbon atoms is divided into two isomers 1,2,3-triazole and 1,2,4-triazole. Compounds containing triazole are one of the siginificant heterocycles that exhibit broad biological activities, such as antimicrobial, analgesic, anti-inflammatory, anticonvulsant, antineoplastic, antimalarial, antiviral, antiproliferative and anticancer activities. A great quantity of drugs with triazole structure have been developed and proved，for example ketoconazole, fluconazole, etc. Given the importance of the triazole scaffold, its synthesis has attracted much attention. This review summarizes the synthetic methods of triazole compounds from various nitrogen source in the past 20 years.